Basal Histamine H4 Receptor Activation: Agonist Mimicry by the Diphenylalanine Motif. Issue 64 (16th October 2019) - Wifling, David; Pfleger, Christopher; Kaindl, Jonas; Ibrahim, Passainte; Kling, Ralf C.; Buschauer, Armin; Gohlke, Holger; Clark, Timothy
Abstract: Histamine H4 receptor (H4 R) orthologues are G‐protein‐coupled receptors (GPCRs) that exhibit species‐dependent basal activity. In contrast to the basally inactive mouse H4 R (mH4 R), human H4 R (hH4 R) shows a high degree of basal activity. We have performed long‐timescale molecular dynamics simulations and rigidity analyses on wild‐type hH4 R, the experimentally characterized hH4 R variants S179M, F169V, F169V+S179M, F168A, and on mH4 R to investigate the molecular nature of the differential basal activity. H4 R variant‐dependent differences between essential motifs of GPCR activation and structural stabilities correlate with experimentally determined basal activities and provide a molecular explanation for the differences in basal activation. Strikingly, during the MD simulations, F169 45.55 dips into the orthosteric binding pocket only in the case of hH4 R, thus adopting the role of an agonist and contributing to the stabilization of the active state. The results shed new light on the molecular mechanism of basal H4 R activation that are of importance for other GPCRs. Abstract : How does it work? In addition to ligand‐dependent G‐protein‐coupled receptor (GPCR) activation, which has been studied intensively, GPCRs can also be activated spontaneously in the absence of a ligand. This study highlights the mechanisms behind such basal GPCR activation by using the example of the H4 R, a GPCR with extraordinarily high basal activity.